Internal Energy, Enthalpy and Gibb’s Free Energy of Spinning Black Hole in Active Galactic Nuclei (Bulletin of Pure and Applied Sciences – Physics, 2022)
The present paper gives a model for the change in the internal energy and enthalpy  (Mahto et al., 2016) and reviews it to propose a model for change in Gibb’s free energy  of the Reissnner-Nordstrom black hole. This also calculates their values in AGN  concluding that the enthalpy and internal energy has the same values and they are just  double to that of Gibb’s free energy for the same mass.